Two‐year outcomes of minimally invasive XEN Gel Stent implantation in primary open‐angle and pseudoexfoliation glaucoma. Issue 4 (30th September 2020) - Rauchegger, Teresa; Angermann, Reinhard; Willeit, Peter; Schmid, Eduard; Teuchner, Barbara
Abstract: Purpose: The aim of this study was to evaluate the efficacy of XEN ® Gel Stent implantation in the treatment of primary open‐angle glaucoma (POAG) and pseudoexfoliation glaucoma (XFG) regarding the reduction of intraocular pressure (IOP) and number of IOP‐lowering medications over 2 years. Methods: In this retrospective, observational, single‐centre study, patients with POAG or XFG underwent implantation of the XEN ® Gel Stent with or without combined phacoemulsification. Changes in mean IOP, mean number of IOP‐lowering medications, number of postoperative interventions, complete or qualified surgical success rate (defined as IOP < 18 mmHg without or with IOP‐lowering medication, respectively) and complete surgical failure rate (defined as the necessity of a glaucoma‐related secondary surgical intervention or loss of light perception) were assessed 12 months (12M) and 24 months (24M) postoperatively. Results: Seventy‐nine eyes of 63 patients with open‐angle glaucoma were included in the study (71% POAG, 29% XFG). Before surgery, mean IOP was 23.4 ± 7.9 mmHg. IOP was 14.6 ± 3.6 mmHg 12 months postoperatively (−31% from baseline, 95% CI −42% to −20%, n = 30, p < 0.001) and 14.8 ± 4.4 mmHg 24 months postoperatively (−29% from baseline, 95% CI −30% to −41%, n = 28, p < 0.001). Mean number of IOP‐lowering medications was significantly reduced from 2.7 ± 1.1 before surgery to 1.0 ± 1.2 (−69%, 95% CI −89% to 46%, p < 0.001) 12 months after surgery and 1.0 ± 1.2 (−64%, 95% CI −91% to −36%, p < 0.001) at 24 months after surgery. Complete surgical success was achieved in 39% (12M) and 34% (24M) of patients and qualified success in 29% (12M) and 27% (24M). 13 (16%) eyes were classified as complete surgical failure. In 62% of the patients needling procedures had to be performed. Conclusion: The XEN ® Gel Stent is an efficacious minimal invasive glaucoma surgery for primary open‐angle and pseudoexfoliation glaucoma, resulting in significant reduction of IOP and a reduction in glaucoma medications from baseline in two‐third of treated patients with 2‐year follow‐up. Frequent follow‐up examinations were mandatory to identify early and late bleb failure and additional needling procedures were necessary to reestablish aqueous flow.